1987
DOI: 10.1002/jbm.820210607
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surface preparation on metal/bone cement interfacial strength

Abstract: This study is concerned with finding practical ways for strengthening metal/bone cement (M/BC) interfaces via surface alterations and identifying fundamental mechanisms underlying M/BC adherence. Shear strengths have been inferred from torsion tests using shear-lag analysis. The variables examined with regard to their effects on interfacial strength are substrate material, surface roughness, interface porosity, passivation and sterilization, surface cleaning procedures, and use of bone cement precoated metals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Cementing techniques [16], surface roughness patches [17], textures [18], and pre-coatings [7,[19][20][21] have been considered to create a reliable and endurable fixation. However, as long as the bond between the stem and the cement mantle cannot be secured for the complete lifetime of the implant, not just the bonding strength, but also the fail-safe mechanism against the effects of debonding should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Cementing techniques [16], surface roughness patches [17], textures [18], and pre-coatings [7,[19][20][21] have been considered to create a reliable and endurable fixation. However, as long as the bond between the stem and the cement mantle cannot be secured for the complete lifetime of the implant, not just the bonding strength, but also the fail-safe mechanism against the effects of debonding should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the bonding forces between stems with different surface finishes and PMMA found an unexplained increase in the bonding force as the stem became smoother (Bundy and Penn 1987). The increased bonding force between increasingly smooth surfaces and the PMMA was ascribed to an atomic (or chemical) interaction.…”
Section: Discussionmentioning
confidence: 99%
“…An increased electrostatic interaction between the metal and bone cement due to van der Waals forces could be involved." (Bundy and Penn 1987).…”
Section: Discussionmentioning
confidence: 99%
“…A roughness of 1 μm was preferred in this study, depending on the findings of previous studies about shear strength and clinical outcome. Around the level of 1 μm, an acute increase in SCI stability was reported, reaching the estimated in vivo shear stresses [4,7]. Although higher levels of roughness provide higher shear strength values, they are not preferred in clinical settings since rough stems have been shown to have higher failure rates compared to polished stems [6].…”
Section: Discussionmentioning
confidence: 99%
“…Shear strength of the SCI is affected by several factors including the stem's surface roughness [4,7,20,21], preheating the stem [12,21], pre-chilling the cement monomer [13], the type of cement used [20], precoating of the stem [1,17], metal type [4], and even the loading rate [22]. Possible effects of all these factors were eliminated in our study, using a standard protocol for all groups.…”
Section: Discussionmentioning
confidence: 99%